PERANCANGAN SISTEM INFORMASI PENJUALAN PADA FJS STICKER BERBASIS WEB - Abdulah Taufik; Dede Abdurahman (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2023)
In the present era, the implementation of IT has been carried out in various fields, including government, healthcare, military, education, economy, and others. All of this is done in order to boost results and facilitate work processes. In the field of economy or trade, IT is utilized to enhance performance and competitiveness with similar companies. This also has a positive impact on profit acquisition and product marketing expansion. E-commerce is one of the advancements in technology and the internet. It is an internet service used for online buying and selling. With e-commerce, many changes have occurred in the process of transactions. Unlike traditional commerce where sellers and buyers meet physically, e-commerce allows them to interact through the internet or communicate via telephone or chat. Trust becomes the main asset in this process. Therefore, the aforementioned issue necessitates the presence of an information system that can be used to search for information on ornamental plant locations. To address this issue, a web-based information system called "Design of Sales Information System for FJS Sticker" has been developed.